Best treatments available for distal acquired lacrimal obstruction: A systematic review and meta‐analysis. (6th May 2020) - Vinciguerra, Alessandro; Nonis, Alessandro; Giordano Resti, Antonio; Bussi, Mario; Trimarchi, Matteo
Abstract: Background: Epiphora is a common clinical sign whose primary cause is post‐canalicular lacrimal obstruction. Treatment is both surgical and non‐surgical. In the literature, there is some evidence to suggest that some treatments are superior to others, but there are no direct comparative data in this regard. Objective of review: To analyse the success rates of all available treatments to resolve post‐canalicular acquired lacrimal obstruction. Type of review: Systematic review and meta‐analysis. Search strategy: A literature search was conducted in the US National Library of Medicine (PubMed), EMBASE, SCOPUS and Cochrane databases with a final search performed in January 2020. Evaluation method: The search strategy identified articles published later than 2000 with at least 50 procedures performed both surgically (external dacryocystorhinostomy [EXT‐DCR], endoscopic dacryocystorhinostomy [END‐DCR] and transcanalicular laser dacryocystorhinostomy [TCL‐DCR]) and non‐surgically (balloon dacryoplasty [DCP], probing‐stenting [SP] and polyurethane stent [PoS]). The primary outcome was functional success, defined as symptom resolution or less than MUNK 2 scale; in addition to this, the influence of adjunctive treatments, such as application of mitomycin C and post‐procedural silicone stenting, was evaluated. Results: In total, 14 958 papers were selected, 440 of which were reviewed after screening; 55 were included after full‐text review, which involved 9337 procedures. Mean success rate was 48.9% (35.7%‐62.3%) for DCP, 54.4% (41.8%‐66.5%) for SP, 73.6% (59.7%‐84%) for PoS, 80% (75.1%‐84%) for TCL‐DCR, 89.8% (83.3%‐93.9%) for EXT‐DCR and 89.5% (87.2%‐91.5%) for END‐DCR. Among all procedures, a difference was noted between DCP and END‐DCR ( P < .001), DCP and EXT‐DCR ( P < .001), SP and END‐DCR ( P < .001), SP and EXT‐DCR ( P < .001), END‐DCR and PoS ( P = .016), and END‐DCR and TCL‐DCR ( P = .001); no differences were noted between END‐DCR and EXT‐DCR ( P = 1.00), EXT‐DCR and PoS ( P = .121) and EXT‐DCR and TCL‐DCR ( P = .223). Considering surgical procedures, no differences were seen if a silicone stenting was applied, whereas, due to heterogeneity of the literature data, no statistical analysis was feasible for application of mitomycin C. Conclusions: Our analyses suggest that, among all procedures available, END‐DCR and EXT‐DCR should be considered as treatments of choice to resolve distal acquired lacrimal obstruction.